Reverse Pseudohyperkalemia: An Important Clinical Entity in Chronic Lymphocytic Leukemia. (27th September 2015) - Mansoor, Sahar; Holtzman, Noa G.; Emadi, Ashkan
Abstract : Hyperkalemia is a potentially lethal electrolyte derangement commonly seen in patients with hematologic neoplasms with or without renal failure. Pseudohyperkalemia and reverse pseudohyperkalemia also can be seen in this patient population and early recognition and diagnosis of these conditions are vital. Here, we report a case of reverse pseudohyperkalemia in a patient with chronic lymphocytic leukemia (CLL) and provide recommendations regarding diagnostic and therapeutic strategies for management of such patients. Further, we discuss the pathogenesis of this condition and its potential role as a surrogate of favorable prognostic features in patients with CLL.